A Case of Lime-Induced Phytophotodermatitis - Sousa, Joana; Nogueira, Ana (Gazeta Médica, 2024)
Phytophotodermatitis is a phototoxic reaction caused by combined skin exposure to photosensitizing plants and ultraviolet radiation. Despite being rare, its incidence has increased. We describe a lime-induced phytophotodermatitis case. A 6-year-old girl presented with a 5-day history of brownish linear plaques on the skin. After careful history taking, it was found the child had been cooking a lime pie and got posterior sun exposure. Her brother had similar lesions. Both family members’ lesions healed after a month. Lime-induced phytophotodermatitis is still weakly recognized. Its bizarre configurations and the agents’ ubiquity can lead to misdiagnosis of child abuse. Exhaustive history and physical examination are crucial. It is required to raise awareness of this disease, so physicians can be prepared to identify it, to ensure the safety of the patients and to tranquilize the family.